The role of non-governmental organizations in caring for vulnerable children in Ghana : a case study of youth alive in northern Ghana - Edwin, David Asante (2008)
One of the major concerns in Ghana, like in most developing countries today, is how to manage the influx of children of school age who roam the streets, market places and lorry park during school hours in search of opportunities and a better life. In response, Youth Alive, a non-governmental organization was established to alleviate the vulnerability of street children in the Tamale municipality by providing formal education and skill training in order to create career opportunity for them. The principal objective of this study was therefore to determine the role of the programme in uplifting participants. The study involved a cross-sectional survey conducted with a total of 89 respondents randomly selected from the list of beneficiaries of the programme through questionnairebased interviews, focus group discussions and Participant Observation. Data processing and analysis were done using Epi.- Info software for quantitative data. Focus Group Discussions were recorded and transcribed from the local language by an expert. All other qualitative data collected were collated manually and were useful in the text to explain some of the major quantitative findings. Descriptive statistics show that major factors leading to the street children phenomenon include general poverty, inability of parents to play their roles, increasing population and poor job availability in the rural areas as well as the collapse of the cultural family support system that served as the cushion against disaster and odds. Discussions with respondents show that to a large extent, the programme has fulfilled its objectives of making vulnerable children have a place to call their home, skills training facilities, health support, and have people who help them to grow into responsible adults. However findings show the need for more financial support for the programme to run successfully. It was recommended that more Agencies/NGOs should find more innovative strategies to empower rural communities in other forms of income generating activities such as providing access to skill training and micro-credit facilities that could give better livelihoods to parents and support for families in especially rural areas in the north. Finally, it is recommended that more small-scale studies of this nature should be done in various communities on the issues related to push-pull factors for migration of young people into the cities